Kant’s Thought Formation and the Role of the Mind: A Groundwork for Development - Onah, Ikechukwu; Ugwu, Anayochukwu Kingsley (Conatus - Journal of Philosophy, 2024)
This paper argues that no form of meaningful development can be discussed without an incursion into the realm of consciousness, from which ideas emanate. This paper demonstrates that human civilization is driven by notions such as ideas, imaginations, concepts, plans, and projects which are germane to social development. An examination of Kant’s theory of concept formation reveals that though objects are given to us by means of sensibility, it is through the understanding that concepts arise. The mind therefore becomes the ‘breeding’ ground from which our ideas are generated and organized. In Kant’s analysis of the faculty of understanding, he noted that there are a priori pure intuitions and sets of categories such as Quality, Relation, Modality that organize particular sensations into unified objects of experience. This capacity of the mind enables it to produce or generate ideas within its own operations. Ideas generated are used to recreate our world. This paper provides a conceptual framework to explicate the foundation of development. Using the method of analysis, this essay concludes that the basis of development − social, economic, and cultural − is hinged on the nature and role of the mind.